The Role of Role Playing in Enhancing Students’ Speaking Ability: A Review of Literature in Bahasa Indonesia Education - Zuni Humairoh (Action Research Journal Indonesia (ARJI), 2025)
Speaking skill is one of the essential components of Bahasa Indonesia learning, playing a significant role in developing students’ communication abilities, critical thinking, and self-confidence. However, in practice, speaking instruction in schools often relies on conventional methods that provide limited opportunities for student engagement. This literature review aims to analyze the effectiveness of the role playing method in enhancing students’ speaking skills in Bahasa Indonesia learning. Data were collected through a systematic review of national and international scholarly sources related to the application of role playing in language education. The findings indicate that role playing is effective in improving students’ speaking ability, enriching vocabulary, refining pronunciation, and fostering confidence in public speaking. Moreover, this method creates an active, interactive, and enjoyable learning environment that stimulates students’ participation. Therefore, role playing can be considered a highly applicable instructional strategy to enhance speaking skills in Bahasa Indonesia, particularly at the elementary education level. This review is expected to serve as a reference for educators in selecting innovative, student-centered teaching approaches.